Emotions and Learning: Fostering an Emotional Culture to Transform Education - Natalini, Alessandra (An Overview of Literature, Language and Education Research Vol. 8, 2024)
Research highlights the crucial role of emotions in the learning process, emphasizing that while skills may endure, emotional states profoundly influence how skills are acquired and applied. This contribution aims to underscore the vital role of emotions, which are not merely fleeting reactions but fundamental resources in education, capable of shaping experiences and fostering more meaningful and lasting learning. Emotional engagement enhances motivation, improves retention, and cultivates a positive learning environment. When students connect emotionally with the material, they are more likely to internalize information and develop a lasting understanding. Conversely, negative emotional states can hinder learning, highlighting the importance of creating supportive environments that are sensitive to emotional dimensions. A key concept in this context is emodiversity, or the range and balance of emotional experiences, which plays a transformative role in shaping learning. Research suggests that fostering emodiversity—encouraging students to experience and regulate a wide spectrum of emotions—can enhance adaptability, resilience, and deeper connections with educational content and peers. Recognizing the adaptive nature of emotions and emodiversity allows educators to design strategies that effectively leverage these emotional resources. Techniques that promote emotional awareness, regulation, and diversity can enrich both personal and social interactions during the learning process. By addressing both cognitive and emotional dimensions, including the richness of emodiversity, educators can develop more holistic teaching approaches. This not only respects the interplay between emotions and learning but also harnesses the transformative power of diverse emotional experiences to foster meaningful, enduring educational outcomes that benefit individuals and communities alike.